Estudos para a construção de um espectrômetro Raman de baixo custo - (:unkn) unknown (Universidade Federal do Pampa, 2022)
This dissertation describes the studies needed to construct a low-cost Raman spectrometer. The Raman spectrometer construction is divided into three steps, the first one is the optical arrangement for compound excitation, using a laser as an excitation source, the second one consists of the spectrometer that functions as a wavelength selector, and the third step and last one is the detection system, using a camera as a detection device. By studying the equipment this dissertation intends to show to the community the viability of the technique and the possibilities to develop spectroscopy in the theoretical and instrumental area, as well as in Chemical Engineering, being that this study presents specifically the Raman technique. Physical-chemical phenomena can be explored as well with the use of this tool, like theoretical interpretations that can be realized for molecular vibrations studies. The device development involves an optical simulation, for a posterior design, 3D printing pieces, and finally, data collection. The spectrometer module has been validated by obtaining the mercury spectral lines, while the Raman arrangement for obtaining spectra could not be validated, a fact that is analyzed from a theoretical and practical point of view, resulting in the section of future suggestions, the one that suggests ideas for the encountered problems.
Keywords: Espectrômetro Raman; Faça-você-mesmo; Vibrações moleculares; hardware aberto; Raman spectrometer; Do-it-yourself; Molecular vibrations; Open hardware; CNPQ::ENGENHARIAS